Synthesis of Electroless Ni-P-Cg (graphite)-SiC Composite Coating on Piston Rings of a Small Two Stroke Utility Engine - Bahaaideen, Farhad Bilal (2011)
Electroplating of piston rings substrate of a small two stroke utility engine was carried out. The substrates were electroplated with pure Ni, Ni-SiC, Ni-Cg(graphite)-SiC, and Ni- P-Cg(graphite)-SiC. The plating temperature was fixed at room temperature, pH was regulated from 3.6 to 4.0, and current density was fixed at 30 mA/cm2. For comparison, Ni-P-Cg(graphite)-SiC electroless plating was also studied at 90 °C. The effect of annealing process at 400°C for one hour was also studied for both electroplating and electroless plating of Ni-P-Cg(graphite)-SiC samples. Cross-sections of all samples, including of the uncoated, were studied and analyzed using Field Emission Electron Microscope (FESEM), EDAX, and microhardness. The micrographs showed that the Cg and SiC particles were co-deposited. The coating shows a compact embedding of Cg and SiC particles in the Ni matrix, uniformly and largely distributed in the coating by virtue of mechanical stirring. The microhardness of the uncoated sample was 283 Hv and has been improved to 404 Hv after electroplated with Ni-P-Cg(graphite)-SiC. However, the microhardness has further improved to 844 Hv after annealing at 400°C for one hour. The microhardness of the annealed electroless plated Ni-P-Cg(graphite)-SiC produced even higher hardness at 851 Hv. It was found that the average surface roughness of an uncoated piston ring has improved from 1.095 μm to 0.900 μm and lower friction coefficient of 0.18 compared to 0.23, after Ni-P-Cg (graphite)-SiC composite coating